Adsorpsi Logam Pb2+ dari Limbah Laboratorium Menggunakan Komposit TiO2 – Karbon Aktif Kulit Durian - Keyla Azzahra; Rusdianasari Rusdianasari; Indah Purnamasari (Jurnal Daur Lingkungan, 2026)
Heavy metals are dangerous environmental pollutants known to produce toxic effects on various organ systems in humans and other living organisms. Lead (Pb) is one of the common heavy metals found as a contaminant in the environment, capable of causing a range of negative impacts. This experiment was conducted to analyze the ability of a composite made from TiO2 and activated carbon derived from durian peel to absorb Pb ions present in laboratory waste. Additionally, this experiment also focused on calculating the adsorption kinetics. The activated carbon, weighing 25 grams, was activated with KOH using various solvent concentrations of 2, 3, and 4 M. The activated carbon was then added to 100 ml of titanium dioxide solution, and the mixture was dripped into an STTP-ethanol solution. The sample was stirred for varying durations of 10, 20, 30, and 40 minutes. The sample was filtered and then analyzed using AAS. The optimal time found in this study was 40 minutes, with an adsorption efficiency of 95.45% and an adsorption capacity of 4.2000 mg/g. The adsorption of Pb metal followed the Langmuir isotherm model.